The role of teacher dispositions in overcoming the resistances to change within cyclical processes of training based on research (Lesson Study): A case study - Peña Trapero, Noemí; Pérez Gómez, Ángel Ignacio (Revista Complutense de Educación, 2019)
The case study we show includes the possible reconstruction of one of the essential components of practical knowledge of a teacher of early years: the teaching dispositions (Socket, 2012; Murrel, Diez, Feiman-Nemser & Schussler, 2010). Understanding them as the set of attitudes, values and emotions that condition a posture, a look, a way of being in practice in the classroom (although they are not considered in initial teacher training programs). After using qualitative data analysis techniques, such as observation, in-depth interviews and experience sampling, we have two main conclusions: The first is that action-based strategies, such as the Lesson Study, let the reconstruction of practical knowledge, especially in those teachers with previous dispositions based on the commitment and the intellectual restlessness; And the second is that this strategy let teacher dispositions develop according to pedagogical theories less interventionist.
Keywords: Practical knowledge; Action research; Emotional Intelligence; Professional development